THE SYSTEM OF SUBJECTS OF ANTI-CORRUPTION ACTION IN THE FIELD OF TAXATION AND THE PECULIARITIES OF THEIR ADMINISTRATIVE AND LEGAL STATUS (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that combating corruption in the field of taxation requires a comprehensive approach, which includes institutional reforms, strengthening the independence of anti-corruption bodies, raising social standards, educational initiatives and forming political will. Only through a harmonious combination of these efforts can long-term positive changes be achieved, the transparency of the tax system be ensured and the prerequisites for the sustainable development of Ukraine be created. It is emphasized that an anti-corruption entity is a legal entity, a state authority, a local government body or another institution authorized to implement measures aimed at preventing, detecting, investigating and eliminating the consequences of corruption offenses. The activities of anti-corruption entities are regulated by legislation that defines their functions, responsibilities, competence and mechanisms of influence. It is established that the idea of the effectiveness of anti-corruption entities is formed in the unity of several key aspects. First of all, this is the presence of sufficient authority to perform their functions. In particular, independence is critical to prevent political or administrative influence that could weaken the work of anti-corruption bodies. It is also important to ensure the transparency of their activities, which allows the public and international partners to effectively oversee the activities of these bodies. It is argued that the system of entities involved in combating corruption is formed on the basis of a multi-level approach and includes specialized bodies, such as NABU, NACP, BEB and STS. Each of them has a clearly defined administrative and legal status, which allows them to effectively perform their functions.
Keywords: system of anti-corruption entities; taxation; features; administrative and legal status; interaction; public